Season Variation Abundance of Rynchops niger in the estuary of Cananéia-Iguape-Ilha Comprida, São Paulo - Edison Barbieri (Biota Neotropica, 2007)
This work aims to make available basic information about the occurrence and abundance of the Black Skimmer in the Cananéia-Iguape-Ilha Comprida estuary of São Paulo. Black Skimmer are found throughout the year at the study area. Censuses were made from January to December 2005, on a weekly basis. A total of 48 censuses were completed in each of five areas in the estuary. The results show that Black skimmer was a common species at the estuary and the number of individuals varied among the sites. The Black skimmer was more frequent in the mud flats of the Baixio do Arrozal (Cananéia), in the summer and autumn, in the summer-winter in Boqueirão Norte and Sul and in the autumn-winter in the Baixio of the Boguaçu. All the estuary, the population presented accentuated fluctuations along the year, with the largest seasonal abundance in summer, when the production of the Anchoviella lepidonstole increase.